Case Study: Mobile-Based Application for The Election of The Student Council President in Tegal City - Taufiq Abidin; Slamet Wiyono; Afif Maulana Iskandar (Journal of Computer Networks, Architecture and High Performance Computing, 2021)
The development of information technology at this time has brought big changes for humans, including the way to implement voting. The use of computer technology in the conduct of voting is known as electronic voting (E-Voting). With e-voting, the voting process and vote counting have become more effective and efficient. Election of the head of the student organization at school (OSIS) is an annual event that is held regularly at schools. However, elections are still carried out traditionally. In fact, in the technological era, it should be made more practical. This article discusses the making of a mobile-based application for the student council president election in schools in the city of Tegal. The method used is Waterfall. The resulting mobile application is an application that can be used by the school to make elections, where students can choose directly using a smartphone. The blackbox test results show that the application made is in accordance with the initial design. The whitebox test results show that the application has not found an error. As for the usibility test results, the application made was accepted 80%. However, the user does not like the application interface display with a satisfaction score of only 60%.